The Relationship Of Lean Construction With Project Performance In Construction Companies - Albert, Cheah Chong Hooi (2019)
This study investigates the relationship between lean construction, organisational culture, and project performance in construction companies in Malaysia. Its main objective is to empirically investigate the moderating effect of organisational culture on the relationship between lean construction and project performance. Despite the wide recognition on the role of organisation culture in the implementation of lean construction and their implication on construction project performance, very scant empirical studies that specifically investigated these relationships exist. Additionally, it was meant to determine the dominant culture type in Malaysia construction companies implementing lean construction.